2015
DOI: 10.2169/internalmedicine.54.4248
|View full text |Cite
|
Sign up to set email alerts
|

Features of REM-related Sleep Disordered Breathing in the Japanese Population

Abstract: Objective Rapid eye movement (REM)-related sleep disordered breathing (SDB) is an entity in which the cessation or reduction of breathing occurs primarily during the REM period. Most studies have shown that REM-related SDB more frequently affects women, younger people and patients with mild or moderate SDB. The aim of this study was to prospectively investigate the prevalence and features of REM-related SDB in Japanese subjects compared with the findings of previous reports. Methods A total of 468 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 20 publications
8
23
3
Order By: Relevance
“…In contrast to our study, they found a lower mean BMI among REM-related OSA patients compared to those with NREM-related OSA [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study, they found a lower mean BMI among REM-related OSA patients compared to those with NREM-related OSA [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…32 Congested respiratory tract mucosa due to the hormonal influences of pregnancy might enhance upper airway narrowing. 33 Furthermore, REM-related OSA is more prevalent among women, younger people and patients with mild or moderate OSA, 34,35 and such background factors are consistent with most pregnant women. Thus, pregnancy might cause an increased tendency to develop REM-related OSA.…”
Section: Discussionmentioning
confidence: 94%
“…The dependent variable was the presence or absence of REM-related OSA, and the independent variable was the PSQI. Each model was adjusted for covariates which were selected based on their established clinical difference between individuals with REM-related OSA and NREM-related OSA [2,3,20]. In Model 1, age, gender, and BMI were selected as covariates; in Model 2-a, AHI REM was also included as a covariate, alongside the covariates that were selected in Model 1; in Model 2-b, AHI NREM was also included as a covariate, alongside the covariates that were selected in Model 1.…”
Section: Discussionmentioning
confidence: 99%